Parkin-dependent and -independent degradation of synaptotagmin-11 in neurons and astrocytes. (20th November 2020) - Wang, Yalong; Yan, Shuxin; Zhang, Feifan; Li, Jingchen; Li, Rena; Zhang, Claire Xi
Highlights: Syt11 was a short-lived protein with a half-life of 1.49 h and was degraded by a parkin-dependent UPP in neurons. Syt11 degradation was enhanced by sustained neuronal activity. The degradation of Syt11 in astrocytes had a half-life of 0.58 h. The Syt11 level decreased in astrocytes under chronic hypoosmotic treatment. The degradation of Syt11 in astrocytes was parkin-independent under both isoosmotic and hypoosmotic condition. Abstract: Synaptotagmin-11 (Syt11) is associated with schizophrenia and Parkinson's disease (PD) and is a critical substrate of parkin, an E3 ubiquitin ligase linked to PD. Previously we reported that Syt11 regulates multiple membrane trafficking pathways in neurons and glia. However, the regulation of Syt11 degradation remains largely unknown. As the ubiquitin-proteasome pathway (UPP) plays crucial roles in protein degradation and quality control, we investigated UPP-dependent Syt11 degradation in this study. We found that Syt11 is a short-lived protein with a half-life of 1.49 h in the presence of a protein synthesis inhibitor cycloheximide and is mainly degraded by UPP in neurons. The degradation was further accelerated under sustained neuronal activity and was parkin-dependent. Interestingly, Syt11 had a faster turnover in astrocytes with a half-life of 0.58 h, and UPP partially contributed to its degradation. Mechanical stress applied on astrocytes by hypoosmotic treatment led to reduced Syt11 protein level but increased parkin level. However, the degradation of Syt11 was parkin-independent under both isoosmotic and hypoosmotic condition. Altogether, our results revealed active and distinct proteolytic regulation of Syt11 in neurons and astrocytes.